Constructing diplomatic discourse: a corpus-driven analysis of the discursive strategies by the spokespersons of China's ministry of foreign affairs during a public health crisis - Li, Tao; Pan, Feng (Frontiers in Psychology, 2025)
Drawing on a corpus-driven discourse analysis approach, this paper examines the discursive strategies adopted by the spokespersons of China's Ministry of Foreign Affairs during regular press conferences regarding a public health crisis. The analysis reveals that (1) the spokespersons actively used communicative discursive strategies to articulate China's stance and international cooperation initiatives while also employing offensive discursive strategies to counter criticisms from Western countries and media regarding the virus and the pandemic; (2) Interestingly, a juxtapositional discursive strategy was observed, by which China, together with other countries, was represented as the positive majority, whereas the US and the UK's media BBC as the negative minority, reinforcing the rationality of China's policies. It is argued that the spokespersons' use of discursive strategies can be attributed to China's geopolitical dynamics with the West and the influence of traditional Chinese culture on China's diplomatic policies.